Cross-Cultural Analysis of College Students’ Parental Attitudes Toward Divorce and Child-Rearing - Exploring Interrelationships Among Child-Rearing Variables - Eunjoo Oh (International Journal of Advanced Culture Technology(IJACT), 2025)
This study examines college students’ parental attitudes toward child-rearing and their perceptions of divorce from a cross-cultural perspective. The research aims to explore how these attitudes vary among students from different countries and how their perceptions of divorce relate to their views on parenting. A total of 75 college students (44 males and 31 females) in their early twenties—comprising Korean, Chinese, Vietnamese, and Uzbekistani nationals—participated in the survey while studying at universities in Korea. Four key dimensions of parental attitudes were assessed: guidance, communication, responsibility, and role conflict. Among these, students rated communication with family (M = 3.21) and parental responsibility and confidence (M = 3.17) highest, indicating the perceived importance of active engagement and accountability in parenting. Vietnamese and Uzbek students showed higher levels of involvement, whereas Korean students reflected more autonomy-supportive parenting values. Regarding divorce, Chinese students exhibited relatively accepting attitudes, while Uzbek and Vietnamese students emphasized marital permanence and the necessity of having children after marriage. Statistical analyses confirmed significant differences across cultural groups (ANOVA, p < .05), and strong correlations among the four parenting dimensions (Pearson’s r, p < .001). Regression results further revealed that students’ sense of parental responsibility and confidence significantly predicted the belief that having children is essential after marriage (β = .318, p < .01). These findings highlight the cultural variations in how college students conceptualize parenting roles and family values.